Criteria of selecting and purchasing of the IT security solutions, used by retail companies - ILIE, Filip (Archives of Business Research, 2015)
Purchasing behavior of organizations differs from that those of persons. Buying behavior of organizations is the result of decisions, responsible makers within organizations, regarding the purchase of goods and services. Motivation is generally rational, it establish the products and services that will be purchased only on based the technical characteristics of their and not on "sympathy"of the persons in charge of procurement. To purchase products/services at the beginning of each year or semester are set budgets for each department. In case the IT department, at the beginning of year, is established the products/services they will need and a ceiling - overall - on which they can not overcome. Both public institutions and large companies when it comes to a certain value of products they want to buy them, using as the purchase method, the auction. The base of auction is represented by the tender specifications. In it are listed all of the products/services characteristics, so in order to fully satisfy the need of organization/company. The aims of this paper is to find the criteria for the selection and purchase of IT security solutions, used by retail companies and presenting of IT security solutions, on market in Romania. Keywords: IT security solutions, retail companies, purchasing behavior of organizations, decision and the behavior of the collective consumer.